QUEST FOR SELF-IDENTITY: EXPLORING THE DYNAMICS OF THE DEORI TRIBE OF ASSAM - Nirmolia, Lakhya Protim; Prafulla Nath (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Assam, the mother state of Northeast, is the land of tribal communities where more than twenty-three (23) tribal communities have been living from ancient times. Bodo, Karbi, Tiwa, Mising, Deori, Rabha, Dimasa, Hajong etc. are the major tribal communities of Assam. This paper tries to explore the complex process of defining self-identity of the Deori tribe living in Assam, a state of north-east India. The Deori tribe is an indigenous tribal community that have experienced many historical, sociocultural, and political changes during 60-70 years, thus shaping the sense of identity. The approach that draws from sociology, anthropology, and history to find the way involve in the construction, negotiation, and contestation of the Deori identity over time. Through the examination of historical accounts, oral traditions, ceremonial customs, and socio-economic frameworks, the study illuminates the intricate interaction between internal and external elements that have influenced the perception of the self-identity of the Deori tribe. Furthermore, the paper explores the implications of globalisation, modernisation, state policies on the preservation and revival of the cultural identity of Deori tribe. Finally, it delves into the broader discourses on identity formation, indigenous rights, and cultural resilience in contemporary societies. To prepare this paper both historical and explanatory methodologies have been applied by the researchers.